Campaign To Increase The Knowledge Of Health Cadres In Efforts To Prevent Hearing Loss Risks In Commemoration Of World Hearing Day - Andi Roesbiantoro; Budhi Setianto; Agus Aan Adriansyah; Yauwan Tobing Lukiyono; Rizka Dany Afina; Hartatik Nila Karmila; Nikmatus Sa'adah (PROSIDING SEMINAR NASIONAL PENGABDIAN KEPADA MASYARAKAT, 2024)
Hearing loss is a threat to society and is age agnostic, including in the elderly. WHO commemorates World Hearing Day to raise awareness about the importance of ear care. This activity aims to educate health cadres and the community about hearing loss prevention. Socialisation activities were carried out in Wonokromo Village using lecture and question and answer methods. Before and after the socialisation, participants were asked questions to measure their knowledge about ear health. The counselling programme was attended by 74 participants. The pre-test and post-test results showed an increase in knowledge related to ear health and prevention of hearing loss. The mean value of the pre-test was 634, while the post- test increased to 861, showing a significant change (p < 0.05). This socialisation was effective in increasing participants' understanding and knowledge on how to maintain ear health. This is expected to increase public awareness and concern for the importance of hearing health and apply the results of counselling in everyday life. For the sustainability of this programme, it is recommended that education related to ear health be carried out regularly and involve various community groups. In addition, health cadres can be given further training to become agents of education in their neighbourhoods. Collaborative efforts between health, community and government are also needed to ensure equitable access to hearing health information and services.